2002
DOI: 10.1007/s00467-002-0879-1
|View full text |Cite
|
Sign up to set email alerts
|

Reflux nephropathy in transplants

Abstract: Reflux nephropathy, renal scarring after urine infection, typically occurs in infancy. Although vesicoureteric reflux occurs commonly in kidney allografts, grafts have not previously been regarded as likely to be affected by reflux nephropathy, perhaps because older kidneys are considered to have matured out of the risk. Evidence that adult pigs remain at risk of reflux nephropathy challenges that assumption. We therefore reviewed the pathological findings in allograft nephrectomy specimens to look for evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…Young children’s kidneys are seldom used for transplantation, so reflux nephropathy was not expected to occur. However, scars with typical pyelonephritic histology have been reported in transplant nephrectomies,23 and shown to be very common, and often severe, on DMSA (despite never being recognised on ultrasound) 24. This appears to conform closely to Ransley and Risdon’s model for native kidneys,4 with about 70% of transplants with VUR acquiring focal scars after a UTI.…”
Section: Lessons From Reflux Nephropathy In Human Transplants and Insupporting
confidence: 63%
“…Young children’s kidneys are seldom used for transplantation, so reflux nephropathy was not expected to occur. However, scars with typical pyelonephritic histology have been reported in transplant nephrectomies,23 and shown to be very common, and often severe, on DMSA (despite never being recognised on ultrasound) 24. This appears to conform closely to Ransley and Risdon’s model for native kidneys,4 with about 70% of transplants with VUR acquiring focal scars after a UTI.…”
Section: Lessons From Reflux Nephropathy In Human Transplants and Insupporting
confidence: 63%
“…However, scarring does occur in adult kidneys as well. Adult pig kidneys scar as quickly as those of piglets with VUR and UTI 25 and scarring is known to occur in adult mature kidneys transplanted into pediatric patients 26 . Some recent studies have reported that the age may not be a risk factor for renal scarring and the risk in older children is the same 21, 27, 28 or even higher 29, 30 as compared to the younger children.…”
Section: Risk Factors For Rnmentioning
confidence: 99%
“…Also, after KTX, UTI may lead to kidney damage, negatively affecting long-term graft survival by scarring and interstitial injury [57], although precise data for the pediatric population are scarce [810]. UTI management in such patients undoubtedly is more complex compared with UTI in otherwise healthy children, so that extrapolation of data is not always possible.…”
Section: Introductionmentioning
confidence: 99%